Measurement of full-scale phase change material products considering hysteresis. (25th June 2021) - Serikawa, Mao; Mabuchi, Kensaku; Satoh, Makoto; Nozue, Yoshinobu; Hayashi, Yoshihiko; Yokoyama, Masahiro
Highlights: A measurement method to comprehend the hysteresis phenomenon is proposed. Various types of phase change materials (PCMs) are examined in this study. PCMs are classified into two types based on the behavior of the measurement results. Trend of one during heating after cooling is similar to the monotonic heating curve. The other demonstrates a tendency different from the monotonic heating curve. Abstract: Phase change materials (PCMs) absorb and release a large amount of heat during phase changes, which contributes to temperature stabilization. The hysteresis phenomenon occurs when the phases of some PCMs change and this phenomenon should be comprehended and evaluated for the adequate design of PCMs in applications. Although many studies indicate that the phase change temperature during cooling is different from that during heating, information on behaviors between the two processes is insufficient. There is a possibility that the trend during heating after partial solidification is different from that during monotonic heating after 'perfect' solidification, and vice versa. In this study, to comprehend the hysteresis of full-scale PCMs, the behaviors of PCMs were examined by measuring the iterations of both heating and then cooling, and cooling and then heating at various turning temperatures. As a result, PCMs demonstrated different trends depending on their types. Consequently, the types of hysteresis were classified. By this method, the exothermic and endothermic behavior of the specimen as a product can be measured at a slow cooling/heating rate similar to the actual use condition.